The Influence of Social Media and Online Marketing on University Selection Among New Students - Sewata, Lanjakorn (Chalermkarnchana Academic Journal, 2025)
This study aims to examine the impact of social media and online marketing on university selection among prospective students. A mixed-methods research approach was employed, combining a quantitative survey of 150 new students and qualitative in-depth interviews with university marketers and staff. The results indicate that Facebook and YouTube are the most influential platforms for university-related information, followed by Instagram and TikTok. Furthermore, reviews from alumni (40%) and university websites (30%) significantly contribute to students’ trust in selecting a university, while Influencer Marketing and online advertisements have a lesser impact. Students’ university decisions are primarily influenced by university reputation (35%) and academic programs (30%). However, universities face challenges in budgeting and high competition in online marketing. The findings suggest that universities should adopt effective digital marketing strategies, including leveraging alumni testimonials, producing engaging video content, and utilizing the most impactful social media platforms.